1996
DOI: 10.1164/ajrccm.153.5.8630606
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin A levels in bronchial samples during mechanical ventilation and onset of nosocomial pneumonia in critically ill patients.

Abstract: Local immunoglobulins play a key role in host defense against lung infection. We investigated the pattern of evolution of bronchial albumin, IgA, and IgG levels in ventilated ICU patients in relation to nosocomial pneumonia. Immunocompetent, critically ill patients underwent serial blood and bronchial protein determinations on Day 1 (intubation day), and on Days 3, 7, 10, and 14. The variations in proteins levels were compared with corresponding Day 1 values in the whole population, and between patients who de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…18 Others found that sputum IgA levels correlate inversely with tracheal cell adherence by bacteria. 19,20 An increased adherence indicates increased vulnerability to bacterial invasion by those organisms.…”
Section: Discussionmentioning
confidence: 99%
“…18 Others found that sputum IgA levels correlate inversely with tracheal cell adherence by bacteria. 19,20 An increased adherence indicates increased vulnerability to bacterial invasion by those organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple components defend this border, the strategic molecule of mucosal immunity is secretory immunoglobulin A (sIgA) [7]. This protein binds pathogens at the mucosal border and prevents their attachment to the mucosa and tissue invasion, thereby protecting the host from pneumonia [8,9].…”
mentioning
confidence: 99%
“…Aspiration of saline lavages from distal bronchioles using fiberoptic bronchoscopy and simultaneous measurement of blood urea nitrogen allows calculation of the volume of ELF recovered by the equation: volume ELF (mL) = (mg urea in BAL)/(plasma urea concentration in mg/mL). 133,134 This technique can be applied to determine IgA and cytokine concentration changes in ELF and well as changes in ELF itself. Samples were obtained for analysis from 12 trauma patients sustaining severe blunt injury who were expected to require intubation for a minimum of 5 days in the ICU.…”
Section: Organ-specific Inflammatory Responses Of the Acquired Immunementioning
confidence: 99%